Coastal, valley, and oasis interaction: Impact on the evolution of ancient populations in the south central Andes - Varela, Hector Hugo (2014)
The existing biocultural links are analyzed among ancient inhabitants of the Cochabamba valleys (Bolivia) from the Formative and Tiwanaku periods, coastal and inland Azapa region (Chile) from the Late Archaic to the Late periods, and the Atacama Desert oases (Chile) from the Formative period to the time of European contact. Craniometric information obtained from a sample of 565 individuals from different sites of the studied regions was evaluated using methods derived from quantitative genetics and multivariate statistical analysis techniques. It is shown that during the Formative and Tiwanaku periods inhabitants of the Cochabamba valleys maintained contact with the population of northern Chile. This contact was more fluid with the people from the interior valley of Azapa than it was with the settlers of San Pedro Atacama (SPA). An important biological affinity in the Late Period between the inhabitants of the Azapa valley and the late SPA groups is also examined. The Late-Inca Catarpe SPA sample shows a broad genetic variability shared with the majority of the groups studied. The results reaffirm the differences between the coastal and interior Azapa valley groups and strengthen the hypothesis of two pathways to populating the south central Andean area. The divergence observed among subpopulations can be explained by the spatiotemporal dispersion between them, genetic drift dispersion compensated by the action of gene flow, and cultural norms that regulate within group mating.